2017
DOI: 10.1016/j.ijhydene.2016.12.112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of laser-processed thin ceramic membranes for electrolyte-supported solid oxide fuel cells

Abstract: By laser machining we have prepared thin and self-supported yttria stabilized zirconia (YSZ) electrolytes that can be used in electrolyte-supported Solid Oxide Fuel Cells for reducing the operation temperature. The membranes, which are supported by thicker areas of the same material, have an active area of ~20 µm in thickness and up to 8 mm in diameter. Buckling limits the maximum size of the thin areas to below 1 mm, the overall effective active area being formed by multiple thin areas bounded by ribs. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…3c and g) and corrugated cells (Fig. 3d and h), overcoming the problems reported by Cebollero et al 38,39 Moreover, the same set of gures shows a suitable homogeneous and highly porous microstructure for the different electrodes conrming the high quality of the fabricated cells.…”
Section: Fabrication and Characterization Of High Aspect Ratio 3d Printed Ysz Electrolytesmentioning
confidence: 65%
“…3c and g) and corrugated cells (Fig. 3d and h), overcoming the problems reported by Cebollero et al 38,39 Moreover, the same set of gures shows a suitable homogeneous and highly porous microstructure for the different electrodes conrming the high quality of the fabricated cells.…”
Section: Fabrication and Characterization Of High Aspect Ratio 3d Printed Ysz Electrolytesmentioning
confidence: 65%
“…In fact, we have previously used this technique for preparing thin and self-supporting electrolytic membranes for SOFCs [29]. We have previously reported that the slight roughness produced by the laser ablation mechanism on YSZ surfaces, probably combined with the coating of nanoparticles resulting from the machining procedure, caused a decrease in the cathodic polarisation of about 5% in the 650-850 ºC temperature range [30]. This experimental finding reinforced our initial assumption that laser machining could be an appropriate technique for increasing the density of oxygen reduction reaction (ORR) sites at the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The nominal power is 2 W and the minimum pulse width 5 ns. Additional details of the equipment used and the experimental set up can be found in references [17] and [24].…”
Section: Methodsmentioning
confidence: 99%